Pengaruh Cahaya Terhadap Studio Foto Studio18 Kelapa Gading Jakarta - Wardhana, Sakundria Satya Murti; Mahardika, Muhamad Satria (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2025)
By exploring the influence of natural and artificial light, this study highlights how lighting affects the color, contrast, and dimensions of objects in the final photograph. Using natural light from large windows or skylights can give a photo a soft, natural feel, while artificial light from studio lights allows for greater control over the intensity and direction of the light. This study considers factors such as light source, intensity, and the latest technology, such as LED lights with adjustable color temperature. This study uses a qualitative approach to explain the problem and focus of the study in depth. It also discusses the use of additional equipment such as softboxes, reflectors, and filters to direct light more precisely and create the desired effect. This study develops key concepts to guide optimal photo studio design, ensuring that lighting supports artistic expression and visual aesthetics to the fullest. Therefore, this study is expected to make a significant contribution to the development of better photo studio interior design that is adaptive to the needs of professional photographers.